CoI-based teaching practices to promote EFL learners’ online discussion in China’s blended learning context / Liu Xiaoxing and Farhana Diana Deris - Liu, Xiaoxing; Deris, Farhana Diana (Universiti Teknologi MARA, 2022)
The Community of Inquiry model (CoI) is a guiding framework for blended learning and online learning and it has been implemented in diverse disciplines. However, the research on how EFL (English as a Foreign Language) teachers can promote students’ engagement in online discussions through the CoI framework is very limited. This mixed-method study aims to investigate effective teaching practices that can promote students’ active participation in online discussions based on the CoI in the blended EFL course. Responses to the survey of CoI and Engagement from 97 undergraduates in a Chinese university and interview transcripts of a focus group were collected as the data. The data were quantitatively analyzed by descriptive statistics and simple/multiple linear regression, and qualitatively by thematic analysis. Results indicated that students’ perceptions of the teaching presence, social presence, and cognitive presence in the CoI had a statistically significant impact on students’ engagement in online discussions. Students’ perceptions of teaching presence had both direct and indirect impacts on their engagement; grading in online discussion forums, the teacher’s timely responses and feedback, and the teacher’s guide in the meaningful discussion were highly-rated teaching practices in promoting students’ online discussion. The findings shed light on how teachers in the blended EFL courses should do in the online discussion to promote students’ language use.